(untitled) - Giladi, Ran (Amsterdam, 2008)
Network processors are the basic building blocks of today's high-speed, high-demand, quality-oriented communication networks. Designing and implementing network processors requires a new programming paradigm and an in-depth understanding of network processing requirements. This book leads the reader through the requirements and the underlying theory of networks, network processing, and network processors. It covers implementation of network processors and intergrates EZchip Microcode Development Environment so that you can gain hands-on experience in writing high-speed networking applications. By the end of the book, the reader will be able to write and test applications on a simulated network processor.
Keywords: Network processors,Routing (Computer network management),Packet switching (Data transmission),Bộ vi xử lý khai thác dữ liệu mạng,Routing (quản lý mạng máy tính),Chuyển mạch (Truyền dữ liệu); Equipment and supplies,Equipment and supplies,Thiết bị và vật tư,Thiết bị và vật tư